RANCANG BANGUN APLIKASI GAME MULTIPLAYER SEBAGAI ALAT BANTU PROSES PEMBELAJARAN BERBASIS WEBSOCKET - Aryo Wibowo, Mohammad; Arsa Suyadnya, I Made; Oka Saputra, Komang (Jurnal SPEKTRUM, 2021)
The development of technology information is growing rapidly. For example in the education world, the purpose of interactive learning media is increasingly felt. With that purpose, an ICT-based learning process (Information Communication Technology) can be developed which has the concept of computer and multimedia learning. Computers can be used as a substitute for books and also multimedia can be used as a substitute for teachers when explaining the material. In this study, to give an innovation in the learning models that use quizzes in the learning process, so it would be build a plan of a web socket based of multiplayer game application as a tool for learning process. To making this system, the advantage of web socket is to give a speed in exchanging information on the game system. Finally, the result of this application are to produce a web socket based of multiplayer game system design and how web sockets work when used in a game. The results of the research produce a system design game multiplayer based websocket. Based on BlackBox Testing and websocket testing. the basic needs of the game are functionally fulfilled and the use of the system websocket provides a shorter lag time for requests and responses.